Proletariat Cinema: The Representation of the Working Class In Egyptian Cinema Over 80 Years - Emam, Reham (AUC Knowledge Fountain, 2023)
This thesis explores the representation of the working class “Proletariat” in Egyptian Cinema. One of the main goals of the thesis is to investigate how the working class were depicted in the Egyptian Cinema and film industry over 80 years (1940-2020). What picture of the working class was conveyed to the mass audience, and what messages were eventually hoarded throughout the years? This is a qualitative descriptive study that conducts in-depth interviews with four categories of stakeholders in the Egyptian film industry including film directors, film critics, and film and media scholars. The study explores what values of working-class people have been reflected in Egyptian cinema through its scenarios and implications in film projects and examines whether these depicted values have undergone specific alteration. The thesis also looks at how Egyptian Cinema might have stigmatized the working-class segment through its cinematic representation and character portrayal as accumulated stereotypes and prejudices may influence choices in the societal frame. Throughout these scopes, the thesis looks at stereotyping more closely from a film theory perspective and investigates whether Egyptian Cinema mirrors or molds society.